DIVERSITY IN THE WORKPLACE AND ITS EFFECT ON ORGANIZATIONAL DEVELOPMENT IN BANKING SECTOR. - Pangavhane, Smita B; Gosavi, Y.M. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In the banking sector, workforce diversity is essential for fostering organizational development and driving business success. The rapidly evolving nature of the industry, with its wide range of customer needs and complex regulatory frameworks, requires banks to tap into diverse perspectives to stay competitive. A diverse workforce brings together varied experiences, backgrounds, and viewpoints, which can significantly contribute to innovation, better decision-making, and problem-solving. Banks that embrace diversity are more likely to create products and services that cater to the needs of a diverse clientele, helping them build stronger customer relationships and improve overall performance. Additionally, a diverse workforce enhances organizational culture, promoting inclusivity and respect. This not only improves employee morale but also leads to higher levels of job satisfaction, better employee retention, and a stronger commitment to the organization. By integrating diversity into their organizational development strategies, banks can cultivate a work environment that encourages creativity, collaboration, and productivity. This paper delves into the ways in which banks can leverage workforce diversity to boost organizational effectiveness. It highlights best practices for managing diversity, such as inclusive hiring processes, diversity training programs, and policies that foster an inclusive workplace, ultimately enabling banks to navigate the challenges of a competitive, globalized financial landscape.